Education of Snack Food Safety To Emeyodore Elementary School Students, Sorong City, West Papua - Sukmawati Sukmawati; Ibrahim Ibrahim (Fakultas MIPA Universitas Negeri Padang, 2021)
Snack food plays an important role in providing energy and nutrient intake for school-age children which will support the growth and learning achievement of school children. School-age children are the nation's investment, because children are the nation's next generation. The quality of the nation in the future is determined by the quality of today's children. The safety of safe and healthy food snacks must meet the minimum criteria according to Indonesian national standards in terms of microbiology, chemistry and physics. Efforts to improve human resources must be carried out early, systematically and continuously. The purpose of this service is education on healthy food safety for students at the Emeyodere Elementary School in Sorong City. The service method used is the method of counseling or socializing about healthy snacks. The results of the community service activities showed that the children of SD Emeyedore, especially the second and third graders, were very enthusiastic, because the method used was by providing direct observations about the objects of snacks that were safe and healthy for consumption.